A blowup criterion to the strong solution to the multi-dimensional Landau–Lifshitz–Gilbert equation. (January 2023) - Wang, Guangwu; Guo, Boling
Abstract: In this paper, we will research the regularity of the strong solution to the Landau–Lifshitz–Gilbert equation. We obtain a blowup criterion of the strong solution to the Landau–Lifshitz–Gilbert equation in a multi-dimensional bounded domain with Neumann boundary condition.